OPTIMASI INTERVAL PEMELIHARAAN PENCEGAHAN MESIN BOILER PADA PEMBANGKIT LISTRIK TENAGA UAP UNIT 1 KABUPATEN CIREBON - Wahyu Pratama, Kresna
The need for energy is rapidly growing along with the progress of civilization . One of the basic needs of humans is electrical energy. Its utilization is crucial as a source of energy for electronic devices that assist human life. Simply put, electrical energy needs to be generated through energy conversion methods. The role of generating electrical energy is largely filled by steam power plants (PLTU). In short, PLTU is an electrical energy generator that utilizes kinetic energy from the emergence of steam. This research examines PLTU unit 1 Cirebon with a capacity of 660 MW. This PLTU is built as a coal-fired power plant. The role of generating electrical energy is utilized by the public in the West Java region. Therefore, the performance of each PLTU unit becomes very critical and needs to be considered. PLTU performance is greatly affected by the conditions of critical components within it, including the boiler machine. The boiler machine is expected to be reliability to maintain unit productivity. In maintaining the performance of a system, maintenance factors are important. In this case, the reason are to maintain equipment lifespan, optimize performance, and prevent failures. One way to achieve this is by conducting measured and periodic preventive maintenance. Based on the research conducted, PLTU Unit 1 Cirebon still employs many corrective maintenance strategies. As a result, there are unmeasured repairs and long repair times. This is attempted to be resolved by analyzing the reliability level of machine components. Through this approach, critical components, such as the ID Fan, are identified and studied regarding the optimal interval for preventive maintenance treatments. There are 2 types of repairs, namely light repairs and component replacements. The interval for light maintenance is 43 hours with an expected treatment duration of 5 hours. Meanwhile, the interval for component replacement is 1422 hours with an expected repair time of 212 hours. Through measurements, the proposed conditions can reduce the availability loss value by 37147.44 MWH per year compared to the initial conditions.